21.8k views
3 votes
Help me pleasee (10 points)

Help me pleasee (10 points)-example-1
User Shatia
by
4.8k points

1 Answer

4 votes

Answer:

B

Explanation:

Givens

a^2 + b^2 = c^2

a = 4x

b = x + 2

c = 3x + 4

Solution

(4x)^2 + (x + 2)^2 = (3x + 4)^3 Remove all the brackets.

16x^2 + x^2 + 4x + 4 = 9x^2 + 24x + 16 Collect like terms on the left

17x^2 + 4x + 4 = 9x^2 + 24x + 16 Subtract the terms on the right

8x^2 - 20x - 12 = 0

This factors into

(4x - 12)(2x + 1)

There are 2 answers

4x - 12 = 0

4x = 12

x = 12/4

x = 3

or

2x + 1 = 0

2x = - 1

x = - 1/2

You have to look at x = -1/2 carefully. The problem is that 4x = 4*(-1/2) = - 2 which is not possible in Euclidean Geometry.

So the only answer is x = 3

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.